Considerations for the Strategic Design of the Humanitarian Supply Chain: Towards a Reference Model - Sepulveda-Salas, J (Springer Verlag, 2020)
The strategic design of supply chain is a key factor for organizations, we know that it is not possible to make correct operational decisions if they are not aligned with the strategy of the organization. This same rule applies to humanitarian supply chains, we will not have efficient answers if there is no prior planning. The objective of this research is to identify, on the basis of the Chilean experience and the literature review, the main considerations that should be taken into account when carrying out the strategic design of humanitarian supply chains in order to increase the capacity to respond to natural disasters. The study aims to provide the basic guidelines for the creation of a reference model for humanitarian supply chains, through the identification of the main challenges that humanitarian supply chain management faces today and the critical factors that increase the response capacity of the community. © Springer Nature Switzerland AG 2020.